Biopharmaceuticals : challenges and opportunities - Behera, Basanta Kumara (Boca Raton : CRC Press, 2021)
"This book highlights how traditional microbial process technology has been upgraded for the production of biologic drugs, and evolution of manufacturing process to meet the global market demand with quality products under the guide lines of internally recognised regulatory bodies. This piece of work also carries information on how armed with deeper understanding of life threatening disease, the biopharmaceutical companies or life sciences industries have developed royal scientific heritage of understanding by developing formal and informal partnerships with researchers in institute, universities and other R&D organisation to fulfil the promise of timely quality production with perfect safety and security. One of the most interesting aspects of this piece of work is the conceptual development of personalized medicine (or precision medicine) to get the right treatment to the right patient at the right dose at the earlier stage of development of any inherited disease. Besides this, it also high lights on the most challenging aspects of modern biopharmaceutical science focusing on the most burning topics like design and development of biologic drugs; use of diversified groups of host cells belonging from animals, plants, microbes, insects and mammals; stem cell therapy and gene therapy; supply chain management of biopharmaceuticals; and the future scope of biopharmaceutical industry development. This book is a latest resource for a wide circle of scientists, students and researchers involve in understanding and implementing the knowledge of biopharmaceutical to develop biologics for life saving drugs, and bring awareness on personalized medicines that can potentially offer patients faster diagnoses, fewer side effects and better outcomes. Features: Explains how the traditional cells culture methodology has been changed to fully continuous or partially continuous process. It explains how to design and fabricate living organs of body by 3D bioprinting technology. It focuses on how a biopharmaceutical company confront with various problems of regulatory bodies, and develop innovative biologic drugs. It narrates in detail the update information on stem cell therapy and gene therapy. It explains the development strategies and clinical significance of bio-similars and bio-betters. It high lights on supply chain management of biopharmaceuticals"--
Biopharmaceutical : A New Confront -- Biopharmaceutical Production -- Transitioning from Pharmaceutical to Biopharmaceutical -- Biopharmaceutical from Animal cells -- Plant Biomolecules and Therapeutic -- Biosimilar -- Biopharmaceutical Supply Chain Management.
OCLC-licensed vendor bibliographic record.
Keywords: Pharmaceutical biotechnology; Biopharmaceutics; MEDICAL / Biochemistry; MEDICAL / Pharmacology